PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA BERBANTUAN CANVA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV UPT SDN 27 PASAR KAMBANG KABUPATEN PESISIR SELATAN - Sonya; Anita, Yesi; Andika, Refiona; Febryan Putera, Rafhi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the improvement In Pancasila education learning outcomes using the Problem Based Learning (PBL) model assisted by Canva media in class IV at UPT SDN 27 Pasar Kambang, Pesisir Selatan Regency. This research applies a type of Classroom Action Research (PTK) using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 22 students consisting of 14 men and 8 women. The results of this research show an increase in: a) the first cycle Teaching Module obtained an average of 83,93% (B), and in the second cycle 96,43% (SB). b) The results of the implementation in the teacher aspect of cycle I obtained an average of 81,26% (B), and cycle II 93,75% (SB). c) The results of the implementation of aspects of students in cycle I obtained an average of 76,57% (C), and cycle II 85,15% (B). d) The learning outcomes of students in cycle I obtained an average of 68,81% (K), and sycle II increased to 85,15% (B). Thus, it can be concluded that the Problem Based Learning (PBL) model assisted by Canva media can improve student learning outcomes in Pancasila education learning in class IV at UPT SDN 27 Pasar Kambang, Pesisir Selatan Regency.